Impact of Covid 19 pandemic crisis on the health system and pharmaceutical industry - Almurisi, Samah Hamed; Al Khalidi, Doaa; AL-japairai, Khater Ahmed Saeed; Mahmood, Syed; Chilakamarry, Chaitanya Reddy; Kadiyala, Chandra Babu Naidu; Mohananaidu, Keithanchali (AMG Transcend Association, 2021)
The magnitude of the COVID-19 pandemic has an enormous impact on the health system and pharmaceutical industry in almost every country globally. Health services have been disrupted at many dimensions globally; communicating with patients at homes away from clinics was commonly practiced in order to provide safety actions to the healthcare team. These measures affected the economic income of the hospitals in addition to health insurers as well. Additionally, drug makers' inability to get active pharmaceutical ingredients from Chinese factories was considered another challenge in this situation. The severe interruption of trading and traveling worldwide has resulted in a harmful impact on the real economy. Treatment of coronavirus infection was taken place by different protocols and based on the already existing medications. Most countries race to the rapid development of a vaccine.